Trust in Public and Private Providers of Health Apps and Usage Intentions - Björn Binzer; Jennifer Kendziorra; Anne-Katrin Witte; Till J. Winkler (Business & Information Systems Engineering, 2024)
Abstract Mobile health apps, particularly personal health records (PHRs), play a vital role in healthcare digitalization. However, the varying governance approaches for providing PHR platforms have led to a growing debate on the adequate regulation of health technology with regard to their adoption. This article investigates how provider governance, whether public or private, influences users' intentions to use and decisions to download a PHR app. Drawing on institutional trust, privacy calculus, and privacy control frameworks, the study develops hypotheses about how provider governance affects the pathways through which trust influences users' intentions to adopt the app. Data acquired from an online experiment in the German market reveals that users exhibit a higher level of trust in public providers compared to the same app provided by private companies. Furthermore, provider governance significantly alters the paths in how trust influences usage intentions through perceived benefits, perceived risks, and privacy control. These findings contribute to the development of a sectoral theory of privacy calculus and privacy control in Information Systems (IS). Moreover, they offer practical insights for healthcare regulators and health app providers with the aim of promoting the acceptance and usage of PHRs and other mobile health apps.
Keywords: 330; Mobile health; Digital health; Personal health records; Adoption; Usage intention; Privacy calculus; Privacy control